Women in motion: a proposed intervention strategy to prevent sexual harassment of women on public transportation - de St. Simon, Sophia, author; Holz, Leah, advisor; Goar, Allison, committee member (Colorado State University. Libraries, 2026)
Sexual harassment on public transportation is a persistent and underreported issue, with existing research documenting behaviors such as unwanted comments, non-consensual photography, staring, and physical contact that disproportionately affect women. These experiences can significantly impact individuals’ sense of safety, alter commuting patterns, and contribute to heightened stress and discomfort in daily life. Despite growing attention to harassment in public spaces, there remains a need for accessible, prevention-focused educational resources. The purpose of this project is to examine and raise awareness of sexual harassment on public transit through an educational intervention. Specifically, this project discusses how increased access to clear, researched information and resources may influence individuals’ awareness, bystander responses, and likelihood of reporting incidents. A review-based methodological approach was used to synthesize existing literature, publicly available statistics, and support resources related to sexual harassment in transit environments. These findings helped develop an educational presentation and an accompanying informational poster designed to present key information in an accessible and engaging format. Findings from the reviewed literature indicate that sexual harassment in public transit settings is widespread yet frequently underreported, with meaningful consequences for women’s mobility, autonomy, and psychological well-being. Educational tools that increase awareness of harassment behaviors and available resources have the potential to improve bystander intervention and empower individuals to respond more effectively. This project contributes to the field by bridging the gap between research and practice, transforming empirical findings into practical, user-friendly materials. By emphasizing awareness, accessibility, and prevention, the project supports broader efforts to promote safer and more inclusive public transit environments.
This intervention has not yet been implemented within public transportation systems, and therefore its real-world impact has not been formally evaluated. However, it is designed with the intention of being adaptable for future use in these settings.
The slide presentation and accompanying speaker notes were intentionally structured to present complementary, rather than repetitive, information.
This project was presented at CURC (Celebrate Undergraduate Research and Creativity), a conference that showcases student research and creative work.
Keywords: women; harassment; transportation